Vascular endothelial growth factor (VEGF) impairs the motility and immune function of human mature dendritic cells through the VEGF receptor 2‐RhoA‐cofilin1 pathway - Long, Jinhua (Cancer Sci, 2019)
Dendritic cells (DCs) are potent and specialized antigen presenting cells, which play a crucial role in initiating and amplifying both the innate and adaptive immune responses against cancer. Tumor cells can escape from immune attack by secreting suppressive cytokines that solely or cooperatively impair the immune function of DCs. However, the underlying mechanisms are not fully defined. Vascular endothelial growth factor (VEGF) has been identified as a major cytokine in the tumor microenvironment. To elucidate the effects of VEGF on the motility and immune function of mature DCs (mDCs), the cells were treated with 50 ng/mL VEGF and investigated by proteomics and molecular biological technologies. The results showed that VEGF can impair the migration capacity and immune function of mDCs through the RhoA‐cofilin1 pathway mediated by the VEGF receptor 2, suggesting impaired motility of mDCs by VEGF is one of the aspects of immune escape mechanisms of tumors. It is clinically important to understand the biological behavior of DCs and the immune escape mechanisms of tumor as well as how to improve the efficiency of antitumor therapy based on DCs.